FOOD SECURITY IN SOUTH ASIA: MAJOR CHALLENGES AND SOLUTIONS - N. V. Galistcheva (Vestnik MGIMO-Universiteta, 2018)
The subject of the study is analysis of the state of food security of the South Asian countries at the present time.  The methodological basis of the study is such methods as induction and deduction, analysis and synthesis. The systematic approach to the overall study of the South Asian countries’ economy and the state of its food security in particular has become the base of this research. Historical and statistical method were used to solve the main task of the research to reveal the conditions of the region’s agricultural development and food availability and food accessibility in the region as well as to carry out an assessment of the ability of households to obtain nutritious food all year round. The author also used the comparative method to analyze the South Asian countries’ approaches to realization of food policy that has allowed to reveal the specific tools used by certain countries of the region and the common characteristics of all countries of South Asia.  While selecting the research topics the author proceeded from the idea that the problem of the state of food security of the South Asian countries has not been studied for the last two decades.  The research required to attract and summarize a large amount of statistical data that has been drawn from many sources including official-sites of international organizations and South Asian countries. The author also used Russian and Indian scientific journals and monographs.  The article highlights the state of food security in the region in accordance with criteria offered by the FAO. The author examines the situation in the South Asian countries’ agriculture sector, its productivity, the volume of production, food waste as well as the countries’ dependency on food imports. The article also presents some information on food accessibility which is generally considered within the context of household income, food distribution systems and ability of the household to obtain food seasonally, as well as food consumption within the context of dietary energy consumption and dietary protein and fat consumption.  The author examines all the seven South Asian countries’ national policies for food security aiming at struggle against undernourishment. The author draws the attention to the fact that despite the slight differences in tools they have common aims and tasks. The key directions of national policies for food security include measures to promote big agro-based industries financed by both private and public sector; increase agricultural productivity; enhance agricultural R&D; managing food security risks and vulnerabilities.  The author also notes the steps to aiming the collective food security within the framework of the regional integration group – the SAARC.  The article presents statistical data characterizing hunger and undernourishment trends in South Asia.